MANAJEMEN PERPUSTAKAAN SEBAGAI PENUNJANG HASIL BELAJAR SISWA DI MA NURUL HUDA PRINGSEWU KABUPATEN PRINGSEWU - Husniyah, Waqingah; Masrur, Moh.; Salamun, Salamun (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2017)
Libraries as educational institutions and information provider institutions will have a good performance if supported by adequate management, so that all activities of the institution will lead to efforts to achieve the goals that have been declared. Based on the description above, the researcher is interested to examine more deeply about library management as supporting student learning outcomes. There are five purposes in this research are: (1) describing the meaning of library; (2) describe library technical services; (3) describe library reader services; (4) describe the benefits of libraries for school residents; And (5) to describe the involvement of citizens in the provision of libraries in MA Nurul Huda Pringsewu. Kab. Pringsewu.This research was conducted in MA Nurul Huda Pringsewu. Kab. Pringsewu.dengan using a qualitative approach with case study design. Data collection techniques used include: (1) participant observation; (2) in-depth interviews; And (3) documentation study. Checking the validity of data conducted in this study in several ways, namely: (1) persistence observation; (2) triangulation; And (3) member checks.